Peningkatan Literasi Keuangan Digital Melalui Pelatihan Penggunaan Aplikasi Personal Finance pada Anggota BMT Center Kube Karanganyar - Fathma, Azizah; Adinda Putri Cahyani; Anis Ulul Hikmah; Alam, Azhar (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
The level of digital financial literacy in Indonesia remains below the average of other ASEAN countries such as Malaysia, Thailand, and Singapore. This community service program aims to enhance digital financial literacy among members of BMT Center Kube Karanganyar through training on the use of a personal finance application, FINKU. As a leading cooperative in Karanganyar, BMT Center Kube has consistently provided training and empowerment programs for its members. However, many members still do not manage their personal finances routinely or effectively. The program was implemented using a participatory approach, involving not only the delivery of financial literacy materials but also hands-on practice and discussion sessions on the use of the FINKU application. This application helps users record income and expenses, set budgets, and monitor financial goals through integration with banking and e-wallet platforms. The results of the program indicate an improvement in participants' understanding and practical skills in financial management. Participants began to adopt better financial behavior, including regular financial tracking and more conscious budgeting. Furthermore, enhanced personal financial management among members is expected to contribute to a reduction in the cooperative’s non-performing financing (NPF) rate, which in turn can strengthen the financial performance of BMT and increase beneficial for its members.